Prevalence of Diabetic Retinopathy in Patients of Age Group 30 Years and Above Attending Multicentre Diabetic Clinics in Karachi - Sanaullah Dawar, Tanveer Hasan, Waseem Ullah Memon, Zahid Jadoon, Umair Qidwai, Samina Naz (Pakistan Journal of Ophthalmology, 2018)
Purpose: To estimate the frequency of diabetic retinopathy by age, sex and type of diabetes (Type I & Type II) and to identify possible risk factors for diabetic retinopathy. Material and Method: It’s a descriptive cross – sectional study. During the study 525 diabetic subjects of age 30 years and above were screened at Al-Ibrahim Eye Hospital (AIEH), Diabetic association of Pakistan (DAP), and two primary eye care centres community based diabetic clinics(Gadaap Town and Jamshed Town). Results: Overall mean age of the subjects was 55.3 ( ± 8.9) years with male: female 1: 1.3. The diabetic retinopathy of any grade was detected 28.8% (151 subjects out of 525). Out of them non-proliferative diabetic retinopathy (Mild to severe) was 33.1%, proliferative diabetic retinopathy was 2.65%, clinically significant macular oedema + Non proliferative diabetic retinopathy was 50.33%, clinically significant macular oedema + proliferative diabetic retinopathy was 4.64% and advanced diabetic retinopathy was 9.28%. 85 (56.29%) diabetic patients had uncontrolled diabetes among all retinopathies. Conclusion: Diabetes mellitus and diabetic retinopathy is becoming a major threat to eye health in our community. People with diabetes mellitus should be encouraged to maintain good glycemic control and undergo regular fundus screening (examination) to delay or prevent the development of diabetic retinopathy.